PERAN KEMAMPUAN MENYIMAK DALAM MENINGKATKAN PEMAHAMAN BACAAN PADA SISWA SD - Arianti, Niluh Lisa (Jurnal Sultra Elementary School, 2023)
Listening skills play a crucial role in enhancing reading comprehension among elementary school students. This study aims to review literature on the role of listening skills in the context of interactive learning and strategies that can be implemented to improve listening abilities. The method employed is a literature review analyzing various relevant sources. Strategies such as the use of the talking stick method, group discussions, and educational games have proven effective in enhancing listening skills. This study recommends the implementation of interactive teaching methods in the curriculum to support the development of listening skills and reading comprehension among students.